Przestrzenne zróżnicowanie koncentracji chowu bydła mlecznego w Polsce - Brodziński, Zbigniew (Spatial Differentiation of Breeding Cattle Concentration in Poland, 2005)
In the article GIS (Geographic Information Systems) are used in order to illustrate spatial differentiation of breeding cattle. As we can observe, this kind of method allows presenting chosen characteristics on the basic administration level, that is a commune. Presented analytical maps allow performing estimation of different traits impact on concentration of cattle number in the country.The research results reveal that the concentration of dairy cattle most often occurs in farms which area is between 10-50 ha, where green land covers more than 1/3 of their total area. In the context of concentration of milk production, the areas where the percentage of permanent green land exceeds 30% in the agricultural land structure and the average cattle stock exceeds 43 heads of cattle per 100 ha of agricultural land should be considered prospective areas.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 84-90